A tumor-targeting protein nanoparticle based on Tat peptide and enhanced green fluorescent protein. Issue 12 (25th January 2016) - Guan, Xingang; Li, Chun; Wang, Dan; Sun, Weiqi; Gai, Xiaodong
Abstract : A protein-based nanoparticle containing cell penetrating peptides (CPPs) and enhanced green fluorescent protein (EGFP) was developed through a genetic engineering method. Abstract : A protein-based nanoparticle containing cell penetrating peptides (CPPs) and enhanced green fluorescent protein (EGFP) was developed through a genetic engineering method. In addition to high stability and good biocompatibility, this fluorescent protein nanoparticle also displayed preferential tumor accumulation, indicating its potential application in tumor imaging and anti-cancer drug delivery.